A model for integrating Islamic values and local contexts into mathematics instruction for secondary students - Lateh, Afifi (IAIN Salatiga, 2022)
Islamic integrated instruction connects the teaching of knowledge, concepts, and skills in a particular subject matter with the Quran and the Hadith to promote desirable characteristics in Aqidah, Ibadah, and Akhlaq. This study formulated a model for integrating Islamic values and the contexts of Thailand’s three southern border provinces (Deep South) into mathematics instruction for secondary students. The constructed approach comprised learning activities administered in six steps, including 1) attention-grabbing, 2) presenting contents, 3) validating, 4) building awareness, 5) practical training, and 6) presenting outcomes. Suggestions included teachers exploring and utilizing Islamic content relevant to lessons or local contexts for lessons less related to Islamic knowledge and allowing students to recognize presented mathematic and Islamic bodies of knowledge for further connections to their daily lives.